ANALYSIS OF ART CULTURE POTENTIAL AND TOURISM VILLAGE DEVELOPMENT IN GEGESIK KULON VILLAGE, CIREBON REGENCY - Ratna Puspita Dewi (Bajang Institute, 2022)
Gegesik Kulon tourism village, Cirebon Regency, West Java, is included in the list of 50 the 2021 Indonesian Tourism Village Award (ADWI) event. The village focuses on Tourism development as one of the efforts to revive the economy They are in the midst of the Covid-19 pandemic. Gegesik Kulon tourist village is known to have many potential and the community is still very much preserving the arts and culture. Where the majority of the villagers there work as farmers. Others work as artists and entrepreneurs. In the village that is usually called the Artist's Village many used artistic and cultural heritage so that it is very suitable as a tourist destination for arts and culture education. They are guided by 5 branches art which is also offered as a tourist attraction in Gegesik Kulon Village. Start of fine arts in the form of wood carving, wayang puppets, mask carving, drum crafts, and so on glass painting. This research activity is a field study by conducting observations and interviews on the Potential of Cultural Arts and Tourism Village Development in Gegesik Kulon Village, Cirebon Regency. Where this Gegesik Village holds a lot of tourism potential which during this pandemic can also be used in the future as a work area for the surrounding community. However, the limited presentation of information to tourists makes some local cultural tourism sectors untouched by tourists. Therefore, a mapping of superior cultural tourism objects is made to be implemented into a system that can provide information in the form of locations and descriptions for these cultural attractions.